EXPLORING STUDENTS' EXPERIENCES AND PERCEPTIONS OF AN AI APPLICATION IN QURAN MEMORIZATION LEARNING - Sugiyanto Sam Sugian (IAIN Bone, 2026)
The development of artificial intelligence technology has spurred innovations in education, including the use of an AI Application as a supporting medium for Quran memorization. This study aims to describe students’ experiences and perceptions regarding the use of an AI application in the process of memorizing the Quran at Darussalam Bone Islamic Boarding School. A qualitative descriptive approach was employed, with data collected through online questionnaires distributed via Google Forms to 20 students. The research instrument was designed to explore students’ experiences in using an AI application and their perceptions of its benefits and limitations. The results indicate that using an AI application provides benefits as a supportive medium for memorization, particularly in assisting murojaah (memorization revision), understanding the meaning of verses, and offering flexibility for independent learning. However, the application has limitations in improving recitation accuracy and supporting progress in memorization, mainly due to insufficient features for correcting recitations and limited personal interaction. Therefore, the AI application is considered a complementary tool that cannot replace the role of an ustadz (teacher) in Quran memorization learning. This study recommends further development of an AI Application to make it more accurate, interactive, and aligned with the needs of tahfidz learning in Islamic boarding schools.